Beginning iPhone Development with Swift 3 Exploring the iOS SDK - Maskrey, Molly; Topley, Kim; Mark, David; Olsson, Fredrik; LAMARCHE, JEFF (Apress : Imprint: Apress, 2016)
Assuming little or no working knowledge of the Swift programming language, and written in a friendly, easy-to-follow style, this book offers a comprehensive course in iPhone and iPad programming. The book starts with the basics, walking through the process of downloading and installing Xcode and the iOS 10 SDK, and then guides you though the creation of your first simple application. In this third edition of the best selling book, you'll learn how to integrate all the interface elements iOS users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders. You'll master a variety of design patterns, from the simplest single view to complex hierarchical drill-downs. The art of table building will be demystified, and you'll learn how to save your data using the iOS file system. You'll also learn how to save and retrieve your data using a variety of persistence techniques, including Core Data and SQLite. And there's much more! Beginning iPhone Development with Swift 3 covers brand-new technologies, as well as significant updates to existing tools. You'll have everything you need to create your very own apps for the latest iOS devices. Every single sample app in the book has been rebuilt from scratch using the latest Xcode and the latest iOS 10-specific project templates, and designed to take advantage of the latest Xcode features.